The archaeometric analysis of grave ceramics I: Raetian beakers and lead-glazed set from the eastern cemetery of the Aquincum civil town - Rikker, Balázs; Vámos, Péter; Tóth, Mária; May, Zoltán (Rei Cretariae Romanae Fautorum Acta, 2017)
Rescue excavations between 2005 and 2010 conducted east of the Aquincum Civil Town on the site of the former Gas Factory brought to light some 1300 Roman-period graves. The processing of this large group of finds is being carried out as part of a Hungarian Scientific Research Fund project (OTKA no. 10095 – Study of the archaeological material from the eastern cemetery of the Civil Town of Aquincum, led by Dr Gábor Lassányi). The funding of the project allowed the mineralogical and chemical analysis of a limited number of ceramic finds with archaeometric methods. The phase composition analysis was carried out by X-ray diffraction measurements, while the major and trace elements were analysed by X-ray fluorescence. The aim of the analyses, beyond answering the most important archaeological questions concerning the ceramic finds, was to expand the analytical database of the Aquincum finds for future comparative studies.